Keabsahan Akta Dibawah Tangan pada Kredit Mobil dalam Perjanjian Fidusia - Karnelia, Nazwa (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
In the development of technology and information, developments in means of transportation cannot be separated, which as time changes, always offers the newest forms of technology, even in terms of vehicle design. In its current development, cars are a means of transportation that can be said to be owned by all groups. The need to have this means of transportation makes it possible for consumers who need a car as a means of transportation but it is not always available and accessible to the general public. Non-bank financial institutions exist as an effort to facilitate the community in meeting their needs. Credit is an alternative for the community as an alternative effort to meet existing needs. Fiduciary guarantees are regulated in Law Number 42 of 1999 in order to maintain security in the credit process and to become a credit object registered with the Fiduciary. In legal research, it is explained that the rights and obligations on the part of the consumer are to pay the consumer with the nominal value of the party making the sale and then take back the car as an object of consumer financing guarantee if in the future there is a default. If a default occurs, the buyer is obliged to provide compensation, namely canceling the agreement under compelling circumstances